Comparing the Prevalence and Correlates of Sexual Health Disturbances Among Heterosexual and Nonheterosexual Men: An Overview of Studies. Issue 3 (10th September 2014) - Štulhofer, Aleksandar; Šević, Sandra; Doyle, David Matthew
Abstract Introduction Although sexuality is a central feature that distinguishes nonheterosexual men from heterosexual men, little is known about how sexual orientation influences male sexual function and sexual problems. This presents a challenge for adequate healthcare for gay and bisexual men. Aim The aim of this article is to provide an overview of the literature on the prevalence and correlates of sexual health disturbances among heterosexual and nonheterosexual men. Methods PubMed and PsycINFO databases were searched for relevant studies published in English. Reference sections of selected papers were checked for additional studies of interest. Main Outcome Measures Main outcomes were comparative findings of the prevalence and correlates of sexual health disturbances in heterosexual and nonheterosexual men. Results In total, we found nine studies of interest, five of which used a comparative design. Evidence regarding sexual orientation as a risk factor for male sexual difficulties is mixed, with more recent studies reporting nonsignificant associations. Heterogeneity of sampling strategies and indicators used to assess sexual orientation and sexual function in the studies, as well as the use of relatively small subsamples of nonheterosexual participants, preclude any conclusions about a comparative prevalence of male sexual disturbances. Several studies suggested that rapid ejaculation might be more prevalent among heterosexual than nonheterosexual men. However, a single study that controlled for frequency and patterns of male sexual activity failed to corroborate this finding. Two studies reported similar correlates of sexual dysfunction and sexual problems between heterosexual and nonheterosexual men (e.g., age and depression/anxiety symptoms), but also some sexual orientation‐specific correlates (e.g., body image). Finally, significant but weak associations between minority stressors and sexual health disturbances among nonheterosexual men were reported in two studies. Conclusions There is a lack of comparative assessment of the relationship between sexual orientation and male sexual difficulties. Based on an analysis of the existing studies' limitations, we conclude with recommendations for future studies. Štulhofer A, Šević S, and Doyle DM. Comparing the prevalence and correlates of sexual health disturbances among heterosexual and nonheterosexual men: An overview of studies. Sex Med Rev 2014;2:102–111.